Immunocastrated female pigs’ social and feeding behaviour - Klein D.R. (2022)
© This is an open access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/4.0/), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.This study compared the social and feeding behaviour of immunocastrated female pigs using different immunocastration protocols. We used seventy-two gilts from industrial crossbreeding (Agroceres × Topigs) at 15 weeks of age. The pigs were distributed in a randomised design with three treatments. The second dose of the immunocastration vaccine was applied in two groups, six weeks before slaughter (I6) and four weeks before slaughter (I4). A non-immunised group (NI) was used for comparison. Due to the divergence in the time of immunisation between the two groups, an individual comparison of each immunocastrated group with the control group (NI vs. I6 and NI vs. I4) was performed. Social behaviour was analysed through the collection of images by a monitoring camera, and the analysis period was from 6:00 to 18:00 h, with behaviour observed every ten minutes. Feeding behaviour data were collected by the automated FIRE® system. Anti-GnRH immunisation and the different protocols of application did not influence most social and feeding behaviours.